“We had to be Aware that People are Thinking about this for the First Time”: Interview with Gabriela Bulišová and Mark Isaac - Krondorfer Bjorn; Carr Steve; Nates Tali; Peto Andrea (Eastern European Holocaust Studies)
This interview is available as a Podcast in “Standing Up Against the Assault on Democracy” hosted by the Johannesburg Holocaust & Genocide Centre. Talking to the artists Gabriela Bulišová and Mark Isaac about their current project, “The Landscape of our Memory”, and what challenges we face today when it comes to memory, genocide, and ecocide. The interview was conducted by Tali Nates, a member of the Advisory Board of EEHS (Eastern European Holocaust Studies), Bjorn Krondorfer, Steve A. Carr, and Andrea Pető editor-in-chief of EEHS.